The cutoff values of serum AMH levels and starting recFSH doses for the individualization of IVF treatment strategies - ÖZCAN, Pınar; ÖZCAN, PINAR; Ficicioglu, Cem; ATEŞ, SEDA; ATEŞ, SEDA; GÜNER CAN, Meltem; Kaspar, Cigdem; Akcin, Oya; Yesiladali, Mert (My University, 2017)
Objective: The main purpose of our study is to categorize starting doses of recombinant follicle-stimulating hormone (recFSH) based on various cutoff values of anti-Mullerian hormone (AMH) and to determine the effectiveness of serum AMH levels in the prediction of poor ovarian response.